(untitled) (Journal of the College of Basic Education, 2022)
To identify the target tagged "The effect of generative learning strategy on lateral thinking and the cognitive motivation of mathematics for middle school students", The researcher followed the semi-experimental approach with the post-test, as the researcher prepared a lateral thinking test and a measure of cognitive motivation, which according to the basic sample of (60) students, (30) students for the experimental group who studied according to the generative learning strategy, and (30) students For the control group who studied according to the usual method. After conducting honesty, consistency, and statistical analyzes, the results showed "the effect of generative learning strategy on lateral thinking and cognitive motivation and in favor of the experimental group." In light of the results, the researcher recommended "training teachers of mathematics on the strategy of obstetric learning to apply it in the classroom through courses prepared by the Ministry of Education for this purpose," and she also proposed conducting a pilot study to find out "the effect of generative learning strategy on achievement and creative thinking of mathematics".